Genome-wide association analysis reveals 6 copy number variations associated with the number of cervical vertebrae in Pekin ducks - Xu, Yaxi; Hu, Jian; Fan, Wenlei; Liu, Hehe; Zhang, Yunsheng; Guo, Zhanbao; Huang, Wei; Liu, Xiaolin; Hou, Shuisheng (Frontiers in Cell and Developmental Biology, 2022)
As a critical developmental stage in vertebrates, vertebral column formation process is under strict control. While, we observed variation in the number of cervical vertebrae in duck populations in previous study. Here, we further explored the variation in the number of vertebrae in two duck populations consisting of 421 Pekin duck × mallard F2 ducks and 850 Pekin ducks. Using resequencing data of 125 Pekin ducks with different number of cervical vertebrae and Pekin duck × mallard 352 F2 ducks with different number of thoracic vertebrae, we detected whole-genome Copy Number Variations (CNVs) and implemented genome-wide association study (GWAS) to identify genetic variants related to this trait. Findings verified the existence of variation in the number of cervical vertebrae in duck populations, the number of cervical vertebrae in most ducks was 15, while that in a small part of ducks were 14 or 16. The number of cervical vertebrae had a positive influence on the neck production, and one cervical vertebra addition could increase 11 grams or 2 centimeters of duck neck. Genome-wide CNV association analysis identified 6 CNVs associated with the number of cervical vertebrae, and the associated CNV regions covered 15 genes including WNT10A and WNT6. These findings improve our understanding of the variation in the number of vertebrae in ducks and laid a foundation for future duck breeding.